Diagnostic accuracy of different cross-sectional imaging techniques for disease location and activity in Crohn’s disease and external validation and comparison of MARIAs and IBUS-SAS - Xu, Chenjing; Li, Linzhen; Zhang, Yanyan; Wang, Ruohan; Zhang, Hongjie (Abdominal imaging, 2023)
Purpose The comparative accuracy of cross-sectional imaging techniques for evaluating Crohn’s disease (CD) remains uncertain. This study aimed to assess diagnostic accuracy of disease location and activity in different cross-sectional images and validate and compare International Bowel Ultrasound Segmental Activity Score (IBUS-SAS) and Simplified Magnetic Resonance Index of Activity (MARIAs). Methods CD patients were retrospectively included from August 2018 to May 2021. We compared accuracy of B-mode intestinal ultrasound (B-IUS), computed tomography enterography (CTE), and magnetic resonance enterography (MRE) for the identification of disease location. Meanwhile, disease activity was compared on B-IUS, color Doppler imaging, CTE, and MRE. ROC analyses were used to validate MARIAs and IBUS-SAS. Spearman rank correlation was performed to evaluate the relationships between MARIAs/IBUS-SAS and CDAI, SES-CD, and inflammatory indicators. Results A total of 115 CD patients were evaluated. The diagnostic accuracy of MRE in detecting small bowel disease was superior to that of B-IUS/CTE, showing sensitivity (89.3%), specificity (71.4%), and AUC (0.820). B-IUS had the highest sensitivity (81.2%), specificity (84.8%), and AUC (0.830) for detecting terminal ileal lesions. The diagnostic accuracy for colonic disease and disease activity was not significantly different among these techniques. In the validation of IBUS-SAS, the AUC was 0.860, with an optimal cutoff value to predict active disease of 46.7. MARIAs and IBUS-SAS showed no significant differences in the correlations of CDAI, SES-CD, and inflammatory indicators. Conclusion MRE and B-IUS are more sensitive for detecting small bowel CD and terminal ileal CD, respectively. IBUS-SAS has potential for precisely defining CD activity. Graphical Abstract